Can Brand Loyalty as Mediator Play A Role in The Influence of Perceived Quality and Brand Image on Repurchase Intention? - Santoso, Wahyu; Dari, Seftia Triwulan (Universitas Prasetiya Mulya, 2025)
Bango soy sauce is one of the popular brands that ranks first in the Top Brand Award, but has experienced a decline in the Top Brand Index value starting in 2021, indicating a decrease in consumer repurchase interest. This decline is thought to be related to perceived quality and a weakened brand image. Therefore, this study aims to analyze the effect of perceived quality and brand image on repurchase intention, with brand loyalty as a mediating variable, on consumers of Bango soy sauce in Surabaya City. Surabaya City was purposively selected as the research location, with a focus on modern retail. The sampling method uses accidental sampling with a total of 100 respondents obtained from the Cochran formula. Data analysis using Structural Equation Modeling based on Partial Least Square (SEM-PLS) through SmartPLS 4.0 software. Based on the research analysis, the results show that perceived quality and brand image have a positive and significant effect on brand loyalty. Furthermore, perceived quality and brand loyalty also have a positive and significant effect on repurchase intention. Meanwhile, although brand image has a positive effect, it has no significant effect. In addition, there is also an indirect effect between perceived quality and brand image on repurchase intention through brand loyalty.